Draft Genome Sequence of a Clinical Isolate, Aeromonas hydrophila SNUFPC-A8, from a Moribund Cherry Salmon (Oncorhynchus masou masou) - Han, Jee Eun (American Society for Microbiology, 2013)
We present the genome of a clinical isolate, Aeromonas hydrophila SNUFPC-A8, from a moribund cherry salmon. The completed draft genome of this strain shows high sequence homology to the reference strain A. hydrophila ATCC 7966 (NC008570.1) and known plasmids pAsa2 and pAAk1 from other Aeromonas species (NC004925.1 and NC019014.1).